1999
DOI: 10.1128/jcm.37.12.3879-3882.1999
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Bovine Rotavirus G and P Serotypes in Italy by PCR

Abstract: Determination of the G and P serotypes of group A bovine rotaviruses from 149 samples of feces or intestinal contents collected from calves showing clinical signs of neonatal diarrhea was performed by a nested reverse transcription-PCR typing assay. The G6 serotype was the most prevalent, accounting for viruses in 55.7% of the samples; viruses of the G10 and G8 serotypes were found in 34.9 and 4.7% of the samples, respectively. The virus in one sample (0.7%) was not classified due to concomitant infection with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
45
3
5

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 22 publications
7
45
3
5
Order By: Relevance
“…Bovine group A rotavirus (BoRV-A) is an important pathogen that causes neonatal calf diarrhea (Ishizaki et al, 1996;Fukai et al, 1998;De Verdier Klingenberg et al, 1999;Falcone et al, 1999;Alfieri et al, 2004). Viruses classified as group A rotavirus (RV-A), including BoRV-A, possess two independent neutralization antigens, namely, VP4 and VP7, on the outer capsid, that specify the P type (for proteasesensitive protein) and G type (for glycoprotein), respectively (Estes, 2001;Kapikian et al, 2001).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Bovine group A rotavirus (BoRV-A) is an important pathogen that causes neonatal calf diarrhea (Ishizaki et al, 1996;Fukai et al, 1998;De Verdier Klingenberg et al, 1999;Falcone et al, 1999;Alfieri et al, 2004). Viruses classified as group A rotavirus (RV-A), including BoRV-A, possess two independent neutralization antigens, namely, VP4 and VP7, on the outer capsid, that specify the P type (for proteasesensitive protein) and G type (for glycoprotein), respectively (Estes, 2001;Kapikian et al, 2001).…”
mentioning
confidence: 99%
“…Types G2 and G11 in BoRV-A have been detected using PCRderived cDNA probes (Hussein et al, 1993). Reports on the distribution patterns of these types reveal that P7 [5], P8[11], G6, and G10 are the most common (Fukai et al, 1998;Falcone et al, 1999;Gulati et al, 1999;Okada and Matsumoto, 2002;Alfieri et al, 2004). G8 ranks third among the most common G type www.elsevier.com/locate/vetmic Veterinary Microbiology 123 (2007) [217][218][219][220][221][222][223][224] in BoRV-A, and several G8 strains reported to date have been detected and/or isolated sporadically, or their prevalence has been reported (Sato et al, 1997;Falcone et al, 1999;Fukai et al, 1999;Okada and Matsumoto, 2002;Fodha et al, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Today rotaviral infections are proven to be a common, economically important cause of calf diarrhea throughout the world. Genotypic analyses of a major neutralization protein VP7 of a bovine rotavirus in diarrheal stools collected in different cattle populations throughout the world have shown that the majority of typeable rotavirus isolates belong to G genotypes 6 and 10 (Alfieri et al, 2004;Chang et al, 1996;Falcone et al, 1999;Garaicoechea et al, 2006;Monini et al, 2008;Parwani et al, 1993;Reidy et al, 2006;Snodgrass et al, 1990). Since the first licensed bovine rotavirus vaccine was a monovalent one, monovalent rotavirus vaccine cannot completely protect against heterologous rotavirus infection (Feng et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Field surveys have demonstrated that, so far, G genotype G6 and G10 are the epidemiologically most important bovine rotavirus genotypes worldwide, accounting for 90% of the rotavirus-caused diarrhea approximately. Next to the G6 and G10 genotypes, G8 is the third typical bovine rotavirus genotype (Alfieri et al, 2004;Chang et al, 1996;Falcone et al, 1999;Garaicoechea et al, 2006;Monini et al, 2008;Parwani et al, 1993;Reidy et al, 2006;Snodgrass et al, 1990). In China, our epidemiologic surveillance has shown that rotavirus diarrhea is one of the most important diseases of neonatal calves, and that G6 and G10 were also determined to be the most prevalent genotype of the bovine rotaviruses using nested RT-PCR and sequencing (Chang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%